Спiновi хвилi у феромагнiтнiй нанотрубцi. Урахування дисипацiї та спiн-поляризованого струму - Kulish, V. V. (Publishing house "Academperiodika", 2019)
Dipole-exchange spin waves in a ferromagnetic nanotube with a circular cross-section have been studied in the presence of a spin-polarized electric current. The exchange and dipole-dipole magnetic interactions, anisotropy, dissipation effects, and the influence of a spin-polarized current are taken into consideration. An equation for the magnetic potential of spin excitations in the system concerned is derived, and the dispersion relation for spin waves is obtained. Depending on its direction, the spin-polarized current is demonstrated to either strengthen or weaken the effective dissipation. A condition, under which the presence of the spin-polarized current can lead to a generation of a spin wave, is determined.